Immigrants' perceptions of smart sanctions Zimbabwe - Motaung, Thabo Petrus (My University, 2018)
Despite South Africa experiencing an influx of about 2,5 million migrants from Zimbabwe at the same period that smart sanctions were imposed on carefully selected officials of the Zimbabwean government and other business entities, lived experiences of smart sanctions from these immigrants had not been explored and thus remain unknown. A qualitative case study was undertaken where interviews were conducted with adult male and female participants with the aim of understanding the underlying causes for the influx of Zimbabwean immigrants into South Africa. Whereas the conceptual framework was focussed on relationships between smart sanctions and human security, the contextual framework was underpinned by the perceptions of Zimbabwean immigrants on their lived experiences when smart sanctions were deployed in their country. To this end the study’s theoretical framework was rooted in human security as contemplated by the United Nations’ (UN) Human Development Report of 1994. Data analysis revealed that poverty, unemployment, inflation and collateral damage to citizens at household levels represented the human security risks that drove the influx of Zimbabwean immigrants into South Africa mainly between 2001 and 2009. As a consequence, the ‘precision’ and ‘selectiveness’ which embodied the adoption of smart sanctions as a policy alternative by the international community was repudiated.
Dissertation submitted in partial fulfilment of the requirements for an award of a degree of Master of Management in Security Studies, 2018
Keywords: Zimbabwe--Politics and government.; Zimbabwe--Economic conditions--21st century